MONITORING AGRICULTURAL DROUGHT IN REGIONS OF IRAQ USING REMOTE SENSING TECHNIQUE - Fatima. A. A; Al-Timimi, Y. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The phenomenon of drought is one of the most significant environmental and climatic extreme events; it is more complex in terms of measuring, monitoring, and identifying the possible effects and hazards associated. The remote sensing index, which included the Vegetation Health Index (VHI), was used to describe the geographic and temporal distribution of the springtime agricultural drought. VHI can be calculated based on the Temperature Condition Index (TCI), Vegetation Condition Index (VCI), and Normalized Difference Vegetation Index (NDVI) derived from MODIS Terra satellite data. The outcomes showed that the droughts in the years 2001–2002, 2008–2009 were the most extreme in twenty-two years. The drought years 2001-2002 were followed by the drought-free years 2002/2003,2008/2009. The years 2017-2018 show this phenomenon distributed mostly in the south and southwest bearing. According to the findings, the southwest and western regions are more vulnerable to drought. The results of the drought index VHI indicate that the country is facing non-uniform cycles of drought for all types of droughts. Also, the results showed that there is a negative significance between rainfall and extreme, severe, and moderate drought, even if there was no substantial negative link between rainfall and dryness. It is recommended to adopt the VHI index to monitor the desiccation of vegetation in semi-arid areas with little access to surface meteorological information.